Seroprevalence of Cystic Echinococcosis Using Recombinant Antigen B-ELISA in North Khorasan Province, Northeast of Iran - Reza SHAFIEI; Fatemeh TAGHASI; Seyed Ahmad HASHEMI; Yaser PANAHI; Nasir AREFKHAH; Mostafa OMIDIAN; Farzane ARIANFAR; Farzane ARIANFAR; Zohreh MOSTAFAVI-POUR; Bahador SARKARI (Tehran University of Medical Sciences, 2021)
Background: Cystic echinococcosis (CE) is one of the most important helminthic parasitic diseases in Iran. The current study aimed to assess the seroprevalence of CE in North Khorasan Province, Northeast of Iran in 2018. Methods: The study was carried out in seven cities of North Khorasan Province. Venous blood samples were collected from 932 individuals referring to health centers of those seven cities. A questionnaire was used to obtain the data regarding the subject's gender, age, residence and risk factors linked to the hydatid cyst. Sera samples were evaluated for anti-hydatid cyst antibodies in an ELISA system, using a recombinant B8/1 antigen of E. granulosus. Results: Of the 932 recruited subjects, 496 (53.2%) were male and 436 (46.8%) were female. The range of participants' age was between 11 to 83 yr old and the mean age of the subjects was 35.4 (±12.7) years. Anti-hydatid cyst antibodies were detected in the sera of 37 out of 932 subjects, corresponding to a seroprevalence rate of 3.96%. From these, 20 (54.05%) were male and 17 (45.95%) were female. There were no associations between seropositivity to hydatid cyst and age, the gender of the participants, residential areas and having contact with dogs (P>0.05). Conclusion: CE is relatively prevalent throughout the North Khorasan Province in the Northeast of Iran. Rate of CE infection in this Province is somewhat similar to the rate of infection in other parts of the country.